Epistemology and Education - Andrew Stables (MDPI AG, 2017)
While philosophy of education is often considered an applied discipline, it has made contributions across the philosophical spectrum. For example, there has been a significant body of work on aesthetics and education. There have been occasional incursions into debates about ontology and even, albeit rarely, metaphysics. However, the majority of work has always been concerned with epistemology (questions of knowing) and ethics (questions of right action). Traditionally, much of this work, particularly in epistemology, has had a highly individualistic tendency. The assumption of the knowing mind as key characteristic of the rational autonomous agent is at the heart of the liberal educational tradition and takes root in Descartes' cogito: even if I doubt who I am, there is an 'I' that doubts, and this 'I' is the fundamental characteristic of the autonomous rational agent, the fully human being.